Response analysis of Pinus sibirica to pine wood nematode infection through transcriptomics and metabolomics study - Zhang, Jiawei; Ye, Lingfang; Chen, Qiaoli; Wang, Feng (Frontiers in Plant Science, 2024)
Pinus sibirica is primarily distributed in Siberia. Owing to its excellent cold resistance and development potential, it has become an important introduced tree species in the Greater Xing'an area of China. Pine wilt disease, triggered by the pine wood nematode (PWN, Bursaphelenchus xylophilus), constitutes a profoundly critical affliction within forest ecosystems. Its incidence has extended to the northeastern region of China in recent years. To explore the potential host status of P. sibirica in the Greater Xing'an area for PWN and to elucidate the responses following inoculation, artificial inoculation, transcriptomics, and metabolomics methods were used. In the artificial inoculation experiments, quantitative analysis of nematode populations within the trees demonstrated that PWN exhibited normal growth and reproductive capabilities within P. sibirica. Subsequently, transcriptome and metabolome sequencing were conducted at four time points before disease onset (3-, 5-, 7-, and 9-days post inoculation). Gene trend analysis and differentially expressed gene screening were employed and the results indicated that genes associated with the flavonoid biosynthesis pathway exhibited predominant enrichment among the up-regulated genes. Metabolome analysis showed that the abundance of flavonoid-related metabolites in P. sibirica increased after inoculation with PWN. Integrated analysis of transcriptome and metabolome revealed that after PWN inoculation in P. sibirica, two chalcone synthase (chs) genes and a chalcone isomerase (chi) gene were significantly upregulated, and the upregulation should accumulate naringenin, pinocembrin, and apigenin to help P. sibirica resist infection of PWN.